Aldol condensation of 2,5-dimethoxybenzaldehyde with acetone under basic condition - Mohd Shah, Siti Aminah; Ahmad, Faujan; Abdull Manap, Mohd Rashidi (Oriental Scientific Publishing Co., 2010)
Mixed aldol condensation of 2,5-dimethoxybenzaldehyde and acetone with mole ratio of 2:1 in the presence of sodium hydroxide gave an orange-yellowish crystal; identified as 1,5-Bis(22 ,52 -dimethoxyphenyl)penta-1,4-diene-3-one yield 56 to 82 %.